ry-sy=t

Simple and best practice solution for ry-sy=t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ry-sy=t equation:


Simplifying
ry + -1sy = t

Solving
ry + -1sy = t

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add 'sy' to each side of the equation.
ry + -1sy + sy = sy + t

Combine like terms: -1sy + sy = 0
ry + 0 = sy + t
ry = sy + t

Divide each side by 'y'.
r = s + ty-1

Simplifying
r = s + ty-1

See similar equations:

| 5-7x=140-42x | | 11-10x=106-45x | | 3(x+1)=7(x-2)+7 | | 254-4x=41x+24 | | 6x+3x^2+4x^3+x^4-10=0 | | 6-5x+3x^2+4x^3+x^4-10=0 | | 48585885858558585858x=838384744474484 | | x^2+5x=7 | | x-0.8x=20 | | 10(x+5)=5(x+15) | | 2x=40-6x | | 4x-8=52-8x | | 10x+4=4x+40 | | 119-4x=23+20 | | ln(7x-3)=3 | | 8x-32y=64 | | 4(3x+2)+4=9x+3 | | 17x-8y=323 | | 3ab+7ab-ab= | | 6-9x=14-6x | | 4x^2-x+7=7x+4 | | -9*9= | | 9*-9= | | (3x+52)=36 | | 58-6x=7x | | 6x+12=3(2x+4) | | 9y+3-5y=23 | | 6t-14=-10+5t | | 4x+8-12x=5x-(3x+2) | | 3q^2+4q=-2 | | 2x-6y=24whatisy | | 9m+18= |

Equations solver categories